Fatalism and closure - Basson, Marc (My University, 2009)
Abstract In “Fatalism, Incompatibilism and the Power to Do Otherwise” (2003), Penelope Mackie presents new objections to logical fatalism. One of her objections shows that the principle of Closure is invalid. The principle of Closure is the inference principle used by logical fatalism. In this paper, I give a response to Mackie’s objection by drawing a distinction between logical action-fatalism and logical event-fatalism. I argue that whereas logical-action fatalism presupposes Closure and is so susceptible to Mackie’s objection, logical event-fatalism does not presuppose an inference principle that fails by Mackie’s objection.